Comprehensive Analysis of SLC17A9 and Its Prognostic Value in Hepatocellular Carcinoma - Kui, Xue-Yan; Gao, Yan; Liu, Xu-Sheng; Zeng, Jing; Yang, Jian-Wei; Zhou, Lu-Meng; Liu, Xiao-Yu; Zhang, Yu; Zhang, Yao-Hua; Pei, Zhi-Jun (Frontiers in Oncology, 2022)
Background: H Solute carrier family 17 member 9 (SLC17A9) encodes a member of a family of transmembrane proteins that are involved in the transport of small molecules. SLC17A9 is involved in the occurrence and development of various cancers, but its biological role in Liver hepatocellular carcinoma (LIHC) is unclear. Methods: The expression level of SLC17A9 was assessed using The Cancer Genome Atlas (TCGA) database and immunohistochemistry of tumor tissues and adjacent normal liver tissues. The receiver operating characteristic (ROC) and R software package performed diagnosis and prognosis. GO/KEGG function enrichment and co-expression of SLC17A9, Gene-Gene Interaction (GGI), Protein-Protein Interaction (PPI) networks were performed using R, GeneMANIA, STRING. Western blot, real-time PCR (RT-qPCR), immunofluorescence, colony formation, Wound scratch assay, ATP production assays and high connotation were applied to determine the effect of SLC17A9 knockdown on HEPG2 (hepatocellular liver carcinoma) cells. TIMER, GEPIA and TCGA analyzed the relationship between SLC17A9 expression and immune cells, m6A modification and ferroptosis. Results: SLC17A9 expression in LIHC tissues was higher than in normal liver tissues (p<0.001), and SLC17A9 was related to sex, DSS (disease specific survival) and PFI (disease specific survival) (p=0.015, 0.006 and 0.023). SLC17A9 expression has diagnostic (AUC:0.812; CI: 0.770-0.854) and prognostic potential (p=0.015) in LIHC. GO/KEGG functional enrichment analysis showed that SLC17A9 was closely related to neuronal cell body, presynapse, axonogenesis, PI3K/Akt signaling pathway. GGI showed that SLC17A9 was closely related to MYO5A. PPI showed that SLC17A9 was closely related to SLC18A3. SLC17A9 silencing inhibited HepG2 cells proliferation, migration, colony formation and reduced their ATP level. SLC17A9 expression level was related to immune cells: B cells (r=0.094, P=8.06E-02), CD4+ T cells (r=0.184, P=5.95E-04), macrophages (r=0.137, P=1.15E-02), m6A modification: HNRNPC (r=0.220, p<0.001), METTL3 (r=0.180, p<0.001), WTAP (r=0.130, p=0.009) and ferroptosis: HSPA5 (r=0.240, p<0.001), SLC7A11 (r=0.180, p<0.001), FANCD2 (r=0.280, p<0.001). Conclusion: Our data show that SLC17A9 may influence LIHC progression. SLC17A9 expression correlates with tumor immune infiltration, m6A modification and ferroptosis in LIHC and may have diagnostic and prognostic value in LIHC.